Linking farm diversification, markets, and nutrition: TAFSSA’s Participatory Socio-Agronomic Research - Cheesman, Stephanie; Islam, Saiful; Alanuzzaman Kurishi, A.S.M.; Kamal, Mustafa; Hossain, Shakhawat; Mahjabin, Tasnima; Parvin, Aklima; Parupalli, V.L.B.; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2022)
TAFSSA's Work Package 2 (WP2) emphasizes farm- and landscape-level interdisciplinary research to identify strategies to increase farmers' profits and nutritional yields, conserve resources, and maintain or enhance ecological services, while also mitigating greenhouse gas emissions from farms and agricultural landscapes. Research summaries currently suggest that linkages between farm production and farming household nutrition are not well understood; integrated approaches considering household food production, nutritious diets alongside market systems development are needed. Besides TAFSSA's research platform and on-farm agricultural trials (WP2, Research Protocol 1 and 2), which generate an evidence base for sustainable diversification approaches and are learning sites for the farmer communities involved, this activity explores the influence of other factors (e.g. the access to knowledge on nutrition and/or to marketing strategies, for example the Small Farmer Large Field (SFLF) approach) on the potential for functional and profitable cropping systems diversification.